Research Trend On Fintech Adoption Over the Years: A Bibliometric Analysis - Mansyur, Abdurrahman; Oktaviany, Mega; bin Engku Ali, Engku Muhammad Tajuddin; Makatita, Armin Rusli (Universitas Islam Negeri Alauddin Makassar, 2023)
The rapid development of the fintech industry globally underscores the importance of understanding the factors influencing individuals' or groups' intentions to adopt financial technology. This study employs a bibliometric analysis, utilizing the VOSviewer app on data extracted from the Scopus database, to explore existing research on fintech adoption. A total of 478 documents published from the inception of the field until June 2023 were included in the analysis. The results reveal diverse themes, encompassing various fintech types (Islamic Fintech, Financial Technology (FinTech), Crowdfunding, Electronic Money, Mobile Money, Mobile Payment, Block-chain), dominant variables (Intention to Use, Perceived Risk, Perceived Usefulness, Trust), and adoption theory models (TAM Technology Acceptance Model, UTAUT). This comprehensive overview provides insights into the evolving landscape of fintech adoption research, serving as a valuable resource for academics, researchers, and industry professionals, encouraging further exploration in this dynamic field.